Motivational factors to participate in recreational activities among female undergraduate students of Universiti Putra Malaysia, Serdang - Saleh, Mawaddah (2018)
Although demand for recreational activities among Malaysian are rising, there has been lack of studies conducted focusing on recreation involving female students from universities. The purpose of the study is to identify the motivational factors to participate in recreational activities among female undergraduates students of Universiti Putra Malaysia (UPM) Serdang, Selangor. Data was collected from 150 respondents who are students at UPM. Questionnaire was used to determine the motivational factors in recreation activity among female undergraduate’s students at UPM Serdang. The data was analysed using Mann Whitney U Test. Result showed important motivational factors for UPM female undergraduates students to participate in recreational activities are to increase self-confident, guarantee of good health, stress release, influence of friend and the suitability of facilities provided.